Food knowledge and practices in the Curiaú Maroon community, State of Amapá, Brazil - Viana, Roseane do Socorro Gonçalves (Online Brazilian Journal of Nursing, 2004)
This study is built upon the living conditions and life history of the maroon community of Curiaú de Dentro, in the Brazilian State of Amapá. These conditions manifest themselves in beliefs, values, symbols and representations, which conform and signify the eating practices as bodily and emotional needs. The subjects of this study are the women, men and children of this village, and the object their food habits and beliefs and all the values that speak of food, the body, everyday life and nutrition. The methodology is built on the anthropological, social and anthropometric approaches, making use of participatory observation, application of questionnaires, gathering of anthropometric data. In Curiaú de Dentro, the eating practices reflect the interaction of the afro-descendent culture with the environment, establishing themselves as a strategy to face hunger and periods of food scarcity and abundance. The reflection of the daily food practices of the families can be seen in the high prevalence of acute malnutrition in the children below six years of age, as an indication of the level of food and nutritional insecurity faced by the community, a consequence of the seasonal difference in access to food, the absence of food supplementation programs, inadequate sanitation, and low coverage of health services. The emotions values, perceptions, beliefs and the eating practices perceived in the study reflect the degree of social exclusion in which the inhabitants of Curiaú live.